Ophthalmoplegic migraine and aberrant regeneration of the oculomotor nerve. - O'Day, J (1980)
A patient with ophthalmoplegic migraine developed aberrant regeneration of the oculomotor nerve. This finding supports the view that the oculomotor nerve lesion in ophthalmoplegic migraine is peripheral, but its rarity suggests that the underlying mechanism may be ischaemic rather than compression by an oedematous intracavernous internal carotid artery.